Newsroom gatekeeping and attitudes of community newspaper editors towards citizen journalism - Mahlangu, Johanna Charlotte (My University, 2021)
Citizen journalism has the potential to enhance the state of community newspapers. The emergence of digital media brought about the concept of citizen journalism, allowing ordinary citizens to practice journalism similar to professional journalism. The resultant high volume of news information from ordinary citizens, despite its benefits, leaves editors grappling with what enters the news gate. This study investigated the perceptions and attitudes of editors of community newspapers in Limpopo province of South Africa towards integrating citizen journalism into their daily journalism practices. This qualitative study used interview guide for data collection from a total of six (7) community newspaper editors in the province. The findings of the study indicate that most editors of community newspapers have positive perceptions towards citizen journalism. They are of the view that it could contribute positively towards their organisations particularly in strengthening democratic participation as a corner stone of community media, increasing the circulation of their newspapers, and assisting their communities to strive and strengthen their relationship with the outside world. However, they are not keen to incorporate citizen journalism in their professional practices. Their expressed concerns are lack of ethics and other basic journalistic skills in citizen journalism and the possibility of encumbering the process of news gatekeeping. However, due to many positive impacts of citizen journalism, editors should endeavour to find ways to incorporate citizen journalism into their organisations. Keywords: Gatekeeping, citizen journalism, community newspapers, community participation, news editors
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2021
Keywords: Gatekeeping; Citizen journalism; Community newspapers; Community participation; News editors; Journalism -- Philosophy; Journalism -- Technological innovations; Mass media -- South Africa; Community newspapers; News ombudspersons; Citizen journalism